"They're Losers, but I Know Better": Intra-Fandom Stereotyping and the Normalization of the Fan Subject - Stanfill, Mel (Critical studies in media communication, 2013)
It has become something of a truism in media studies that fans are now free of the old stereotypes to which they were formerly subject and have been mainstreamed as a model for the new ideal active media consumer. However, when speaking to some of these fans, it is evident that they do not feel particularly mainstream. Through interviews with Xena: Warrior Princess fans, I demonstrate that longstanding conceptions of fans as losers who behave badly influence the ways fans understand fandom. However, though they accepted negative portrayals of fans as valid, my interviewees refused to take on that meaning for themselves, instead bracketing themselves out of it and shifting it off onto others. This simultaneous acceptance and refusal of stereotypes suggests that being a fan is a subject position fraught with baggage from historical and contemporary media representations, which troubles triumphalist renderings of a new media order centered on the fan.